1981
DOI: 10.1159/000250156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beta-Carotene in Combination with Canthaxanthin, Ro 8–8427 (Phenoro®), in Treatment of Polymorphous Light Eruptions

Abstract: 50 patients with polymorphous light eruptions were treated with a β-carotene-canthaxanthin combination, Ro 8–8427 (Phenoro®) at a daily dose of 100 mg or placebo for a duration of 10 weeks in a double-blind, randomized, cross-over trial. The effect of treatment was evaluated clinically on the basis of occurrence of pruritus, erythema and eruptions as well as subjectively through the patients own opinion about the condition of their skin. Excellent results after treatment with Ro 8–8427 were achieved in 27 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Studies of the effects of β‐carotene on UVR‐induced inflammation in healthy humans have given conflicting results, some showing a reduction in erythema (37) and others no effect (38, 39). An open study of oral β‐carotene combined with canthaxanthin (a xanthophyll carotenoid) in 50 patients with polymorphic light eruption (PLE), suggested benefit (40), but controlled studies failed to confirm benefit of carotenoids in this photosensitivity condition (41, 42). A case–control study of 88 male patients found the incidence of NMSC was inversely related to serum β‐carotene levels (43), but cohort studies show no relationship between β‐carotene intake and development of basal cell carcinoma (BCC) (44, 45).…”
Section: Effects Of Supplemental Antioxidants In Humansmentioning
confidence: 99%
“…Studies of the effects of β‐carotene on UVR‐induced inflammation in healthy humans have given conflicting results, some showing a reduction in erythema (37) and others no effect (38, 39). An open study of oral β‐carotene combined with canthaxanthin (a xanthophyll carotenoid) in 50 patients with polymorphic light eruption (PLE), suggested benefit (40), but controlled studies failed to confirm benefit of carotenoids in this photosensitivity condition (41, 42). A case–control study of 88 male patients found the incidence of NMSC was inversely related to serum β‐carotene levels (43), but cohort studies show no relationship between β‐carotene intake and development of basal cell carcinoma (BCC) (44, 45).…”
Section: Effects Of Supplemental Antioxidants In Humansmentioning
confidence: 99%
“…30 Beta-carotene in combination with canthaxanthin was reported to be therapeutically beneficial in an open study of 50 patients with polymorphous light eruption, although the authors acknowledge the difficulty in maintaining objectivity in clinical assessment in the face of overt clinical carotenaemia. 31 However, in controlled trials b-carotene has not been demonstrated to have therapeutic efficacy in the treatment of polymorphic light eruption. 32,33 There are no clinical studies which have demonstrated a role for treatment with vitamin E in photosensitivity conditions.…”
Section: Treatment Of Photosensitivitymentioning
confidence: 99%
“…This was unfortunate, as high‐dose β‐carotene has been demonstrated to be safe and well‐tolerated 30 . Beta‐carotene in combination with canthaxanthin was reported to be therapeutically beneficial in an open study of 50 patients with polymorphous light eruption, although the authors acknowledge the difficulty in maintaining objectivity in clinical assessment in the face of overt clinical carotenaemia 31 . However, in controlled trials β‐carotene has not been demonstrated to have therapeutic efficacy in the treatment of polymorphic light eruption 32,33 …”
Section: Treatment Of Photosensitivitymentioning
confidence: 99%
“…This compound is found in several plants, crayfish, salmon, birds, fungi, marine algae and bacteria. Canthaxanthin was discovered for the first time in an edible fungus called Paracoccus carotinifaciens [11,12]. Canthaxanthin can be obtained from biosynthesis or chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%